EUROCENTRISME SEPERTI TERGAMBAR DALAM FILM CINDERELLA (2015) DI PRODUKSI OLEH DISNEY - Meyshara, Andreina Izabella; Wantasen, Isnawati L.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œEurocentrisme dalam Film Cinderella (2015) yang di produksi oleh Disneyâ€ It is written to fulfill the requirement of accomplishing bachelor degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is about eurocentrismand the protagonist characters in the filmCinderella 2015. This research used descriptive qualitative method and the writer used two theories, such as the theory of eurocentriam from Samir Amin in his book entitled Eurocentrism1989 and the theory of character from Edgar V. Roberts in his book Writing Themes about Literature(1983) to identify, describe and analyze the data. Based on the analysis of eurocentrism in the film Cinderella 2015, it was found that the life in this film had European point of view.Keywords: Eurocentrism,Princess, Magic, Film, Disney